EFFECT OF BRAND EQUITY AND MARKETING MIX ON CUSTOMER SATISFACTION AND IMPACT ON CUSTOMER LOYALTY - Sriyani, Nani (EAJ (Economic and Accounting Journal), 2019)
This research is about the activities carried out by PT Bank ICB Bumiputera, Tbk in the use of brand strategy and service marketing mix by looking at its effect on customer loyalty through customer satisfaction.Data processing was done by using path analysis, this research is quantitative with the number of respondents as many as 100 respondents. The results of the first study showed that there is a significant influence between brand equity and marketing mix on customer satisfaction.      The results of the second study show that there is a significant influence of brand quantity, service marketing mix and customer satisfaction on customer loyalty. This research is important information for PT Bank ICB Bumiputera by considering the variables mentioned above so that it can carry out marketing activities that will increase market share and the number of customers